Haemangiopericytoma with no dural attachment. (19th January 2012) - Spence, Emily; Chelvarajah, Ramesh; Shieff, Colin
Abstract : The authors describe a case of a gentleman in his 40s who presented with a space-occupying lesion in the right precentral gyrus which showed no dural attachment and was well circumscribed, both on imaging and at surgery. This lesion was histologically challenging to diagnose but favoured to be a haemangiopericytoma. The lack of dural attachment is unusual for this tumour type but is typically associated with metastases to the brain, and less commonly a solid primary central nervous system tumour. The authors propose that haemangiopericytoma should be regularly considered as a differential diagnosis of cerebral metastases so that inadequate preoperative anticipation and planning is not encountered.